(untitled) (American Journal of Business Management, Economics and Banking, 2025)
This article provides a comprehensive conceptual exploration of digital transformation as it pertains to the economy and labor market, drawing on both classical and contemporary theoretical models. As digital technologies reshape production structures, employment relations, and organizational cultures, the need for a coherent theoretical and methodological framework has become pressing. The study synthesizes key approaches including the Unified Theory of Acceptance and Use of Technology (UTAUT), Skill-Biased Technological Change (SBTC), and organizational change theory to elucidate the mechanisms through which digital transformation impacts work and skills. Methodologically, the article evaluates both qualitative and quantitative traditions, highlighting the rise of mixed-methods and big data applications as essential to capturing the complexity of digital transitions. Attention is paid to the challenges researchers face, including definitional ambiguity, the digital divide, data privacy, and the volatility of technological innovation. Ultimately, the article argues for the development of integrated, multi-level frameworks and policy-oriented research agendas that can inform inclusive strategies for navigating labor market disruptions and supporting sustainable digital growth.